Kajian Enzim Fibrinolitik pada Mikroorganisme Asal Pangan Fermentasi Asia: Review - Syahbanu, Fathma; Pawestri, Setyaning (Jurnal Teknologi Hasil Pertanian, 2023)
Data collected by WHO in 2019 shows an estimated 17.9 million (equivalent to 32% of global death). The total number is due to cardiovascular disease, 85% were due to heart attacks and strokes. One of the basic pathophysiologies of stroke is atero-thromboembolic (thrombosis). The accumulation of clots formed by fibrin in blood vessels can inhibit several processes in the body system, such as blood flow, oxygen transportation, and transportation of nutritional and non-nutritional compounds needed. Fibrinolytic enzymes from food microbes have attracted attention for further research as thrombolytic agents. The Bacillus genus from fermented foods can produce strong fibrinolytic enzymes, such as Bacillus natto from natto (Japan), Bacillus subtilis KCK-7 from Chungkook-jang (Korea), Bacillus weihenstephanensis from shrimp paste (Vietnam), Bacillus amyloliquefaciens MH18B1 from Hawaijar (India), Rhizopus chinensis 12 from Chinese wine (China), and Bacillus pumillus and Bacillus subtilis K2 from fermented soybean food products such as tempe gembus, red oncom, and moromi (Indonesia). The high protein content in soybeans can be used as a medium for the growth of proteolytic and fibrinolytic microorganisms. Studies in Asia regarding fibrinolytic enzymes from fermented foods are still limited, even though the Asian region comprises many countries rich in fermented foods. This review is relevant to healthy food ingredients from local fermented foods. Recently, microbial fibrinolytic enzymes from fermented foods have received tremendous interest in the medical field. Many local fermented foods are a potential source of fibrin-degrading enzymes, which can be further developed to treat diseases like stroke and heart attack. This article aims to review microbial fibrinolytic enzymes from various fermented foods and their impact on health, especially thrombosis. This manuscript review uses the narrative review method. From the overall discussion, it can be concluded that fermented foods have properties as fibrinolytic agents.